Early BCG Vaccination, Hospitalizations, and Hospital Deaths: Analysis of a Secondary Outcome in 3 Randomized Trials from Guinea-Bissau. (18th September 2018) - Schaltz-Buchholzer, Frederik; Biering-Sørensen, S; Lund, N; Monteiro, I; Umbasse, P; Fisker, A B; Andersen, A; Rodrigues, A; Aaby, P; Benn, C S
Abstract : Secondary analysis of 3 randomized controlled trials of BCG vaccine administered shortly after birth versus delayed vaccination in infants weighing <2500g showed that early vaccination did not affect admission rates but protected against in-hospital death, particularly deaths due to sepsis. Study protocols were approved by the Guinean Ministry of Health's Research Coordination Committee and the Central Danish Ethical Committee gave its consultative approval. The trials were conducted in accordance with the Helsinki Declaration ethical standards. Abstract: Background: This study was performed to examine the effects of early BCG vaccination on the risk, cause, and severity of infant hospitalizations. The analysis included 3 trials randomizing low-weight neonates to early BCG vaccination (intervention) versus no BCG vaccination (usual practice in low-weight neonates, control), with hospitalizations as secondary outcome. Methods: Hospitalization data were collected at the pediatric ward of the National Hospital. Effects of BCG vaccination on hospitalization risk were assessed in Cox models providing overall and major disease-group incidence rate ratios (IRRs). Severity was assessed by means of in-hospital case-fatality rates and compared by group as cohort study risk ratios (RRs). Results: Among 6583 infants (3297 in BCG group, 3286 controls), there were 908 infant hospitalizations (450 BCG, 458 controls) and 135 in-hospital deaths (56 BCG, 79 controls). The neonatal (28 days), 6-week, and infant (1-year) BCG versus control hospitalization IRRs were 0.97 (95% confidence interval [CI], .72–1.31), 0.95 (.73–1.24), and 0.96 (.84–1.10). Corresponding BCG versus control case-fatality rate RRs were 0.58 (95% CI, .35–.94), 0.56 (.35–.90), and 0.72 (.53–.99). BCG vaccination tended to reduce neonatal and infant sepsis hospitalization rates (IRR, 0.75 [95% CI, .50–1.13] and 0.78 [.55–1.11], respectively), and it reduced the neonatal in-hospital sepsis mortality rate (RR, 0.46; 95% CI, .22–.98). There were no confirmed hospitalizations for tuberculosis. Conclusions: BCG vaccination did not affect hospitalization rates but reduced in-hospital mortality rates significantly, primarily by preventing fatal cases of sepsis. The observed beneficial effects of BCG on the in-hospital mortality rate were entirely nonspecific. Clinical Trials Registration: NCT00146302, NCT00168610, and NCT00625482.